Affordable Housing And The Well-Being Of Urban Families In Penang Island, Malaysia - Chieng, Samson Kuan Meng (2018)
As Penang Island is going through rapid urban development, there is an obvious growth in the urban population which eventually result in the increase of demand towards housing. The scarcity of land leads to a scenario that pushes up the land use density and values that lead to concerns that are reflected on the well-being of the urban families in Penang Island. The objectives of this thesis are to understand how the urban families in Penang Island define the concept of affordable housing, to identify the issues and challenges faced by urban families in Penang Island pertaining to affordable housing ownership and to analyse the effects of affordable housing on the well-being.